A review of wind loads on canopies attached to walls of low-rise buildings. (1st March 2021) - Sakib, Faruk Ahmed; Stathopoulos, Ted; Bhowmick, Anjan K.
Highlights: Review of state-of the-art methods for wind actions on canopies. Focus on low-rise buildings. Focus on all available wind tunnel studies. Comparison between international codes. Comparison between experimental results and code-prescribed values. Abstract: Overhangs are commonly used in residential and industrial buildings for the convenience of residents and users. Canopies are very prone to wind loading due to the suction developing on their upper surface along with the pressure occurring on their lower surface (for most wind directions), which together may generate critical uplift forces causing serious damage. The paper presents past research on wind effects on canopies of low buildings, originated mainly from atmospheric boundary layer wind tunnel studies. Provisions for wind pressure on canopies in different wind standards and codes of practice are also reviewed. Findings of past and recent studies are then compared with the provisions of various National Codes on wind loading on canopies. Comparisons of the experimental results with some computational results and the provisions of wind codes and standards show significant discrepancies. Some of these differences are due to the variety of configurations used in the previous studies, e.g. building geometry, size and slope of overhangs, canopy location on the wall(s), existence of openings, as well as roof shape (flat, gabled or curved / arched).